2022
DOI: 10.1111/jcpp.13724
|View full text |Cite
|
Sign up to set email alerts
|

Preferential looking to eyes versus mouth in early infancy: heritability and link to concurrent and later development

Abstract: Background: From birth, infants orient preferentially to faces, and when looking at the face, they attend primarily to eyes and mouth. These areas convey different types of information, and earlier research suggests that genetic factors influence the preference for one or the other in young children. Methods: In a sample of 535 5-month-old infant twins, we assessed eye (relative to mouth) preference in early infancy, i.e., before neural systems for social communication and language are fully developed. We inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
3
12
0
1
Order By: Relevance
“…The same specificity has been found for the tendency to look at either the eyes or the mouth, another social attention phenotype that has been found to be highly heritable in both toddlerhood (Constantino et al., 2017) and infancy (Viktorsson et al., 2023). A preference for looking at eyes (vs. the mouth) at 5 months is independent from concurrent development and specifically related to later language comprehension (Viktorsson et al., 2023). These findings suggest that social looking in infancy consists of multiple distinct mechanisms that may be, at least partially, heritable and linked to specific outcomes.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The same specificity has been found for the tendency to look at either the eyes or the mouth, another social attention phenotype that has been found to be highly heritable in both toddlerhood (Constantino et al., 2017) and infancy (Viktorsson et al., 2023). A preference for looking at eyes (vs. the mouth) at 5 months is independent from concurrent development and specifically related to later language comprehension (Viktorsson et al., 2023). These findings suggest that social looking in infancy consists of multiple distinct mechanisms that may be, at least partially, heritable and linked to specific outcomes.…”
Section: Introductionmentioning
confidence: 57%
“…Another study of infant twins found that face preference at 5 months was heritable and linked specifically to verbal competence at 14 months (Portugal et al, 2023). The same specificity has been found for the tendency to look at either the eyes or the mouth, another social attention phenotype that has been found to be highly heritable in both toddlerhood (Constantino et al, 2017) and infancy (Viktorsson et al, 2023). A preference for looking at eyes (vs. the mouth) at 5 months is independent from concurrent development and specifically related to later language comprehension (Viktorsson et al, 2023).…”
Section: Introductionmentioning
confidence: 72%
“…The stimuli used in this study (Non-social condition 36 ; Social condition 37 ; Mixed condition 38 ) were not purposefully designed to measure gaze lateralization, but were used for this purpose as we believe they fulfil the characteristics necessary to answer our research questions. In all three conditions, the sample is based on the same set of infants from BATSS 35 , although the sample varies slightly in each condition due to stimuli-specific exclusion criteria (see specifications in each condition section).…”
Section: Methodsmentioning
confidence: 99%
“…1 ). The primary goal of these stimuli was to measure eye versus mouth looking (already published data 37 ). The videos were shown in a pseudo-random order, unique to each participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation